The Efectiveness of Think Pair Share Model to Impoving Critical Thinking for Student Of Elementary School Education Nusa Cendana University (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
Learning of  Primary School Teacher Education (PGSD) needs to improving with' critical thinking skills. Critical thinking for student in integrated learning, the basis of this research. In this case integrated learning has a low critical thinking ability value. The research will be conducted in PGSD Nusa Cendana Univercity in 4th semester using the think pair share model. The purpose of this study to determine effectiveness of learning includ differences in critical thinking skills and increasing critical thinking skills. The results of this study 1) the ability to think critically for students after learning using the think pair share model that the significance results 0,000 <0.005 that Ho is rejected and Ha is accepted means that there are differences in students' critical thinking skills in the control and experimental class. 2) there is an increase in students' critical thinking skills with the acquisition of N-Gain value of 0.65 which is in the range of 0.70> g> 0.30 in the medium criteria. It can be concluded that think pair share model can improve critical thinking skills of PGSD Nusa Cendana Univercity.